Favourable pregnancy outcome following inadvertent exposure to trastuzumab, tamoxifen and radiotherapy in a patient with breast cancer: a case report - Lamichhane, Deep (Nepalese Journal of Cancer, 2026)
Breast cancer is the most common malignancy among women worldwide and often affects those of reproductive age. Treatment typically involves surgery, chemotherapy, radiotherapy, targeted therapy, and endocrine therapy, several of which are contraindicated during pregnancy due to fetal toxicity. We report a rare case of unrecognized pregnancy in a 28-year-old woman receiving adjuvant therapy for breast cancer. Following excisional biopsy showing infiltrating ductal carcinoma, she underwent neoadjuvant chemotherapy, modified radical mastectomy, radiotherapy, and was receiving trastuzumab with tamoxifen. An ultrasound performed for abdominal discomfort revealed a 32-week viable pregnancy. At the time of diagnosis of pregnancy she was taking daily tamoxifen, on maintenance trastuzumab and in retrospect she had received radiotherapy after conception. She later delivered a healthy baby by caesarean section, and both mother and child remain well at two-year follow-up.